Direct yaw control based on a phase plan decomposition for enhanced vehicle stability. Issue 8 (2019) - Khelladi, Faïza; Orjuela, Rodolfo; Basset, Michel
Abstract: This paper introduces an advanced direct yaw control (DYC) by supervision with the aim of improving the safety of vehicles. The proposed DYC is based on a hierarchical approach and a global stabilizing yaw moment is calculated by combining two different controllers in order to control yaw rate and vehicle sideslip angle. The activation of each controller depends on the critical driving situation detected by the proposed supervisor. The latter is based on a yaw rate - sideslip angle phase plan decomposition by using the limits of the yaw motion variables. Finally, the global stabilizing yaw moment will be distributed on the four wheels through the control allocation by using differential braking.